2022
DOI: 10.1007/s00248-022-02041-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitivity of Microbial Litter Decomposition in Freshwaters: Role of Leaf Litter Quality and Environmental Characteristics

Abstract: Ongoing global warming is expected to alter temperature-dependent processes. Nevertheless, how co-occurring local drivers will influence temperature sensitivity of plant litter decomposition in lotic ecosystems remains uncertain. Here, we examined the temperature sensitivity of microbial-mediated decomposition, microbial respiration, fungal biomass and leaf nutrients of two plant species varying in litter quality. We also assessed whether the type of microbial community and stream water characteristics influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…While climate variables are stronger predictors of wood stake decomposition in the northern hemisphere than soil properties (e.g., pH and C:N), microsite climatic conditions of soil temperature and moisture also influence wood stake decay (Risch et al., 2022). In general, warmer and moister conditions facilitate the wood decay process (Monroy et al., 2022; Piaszczyk et al., 2022). Our first hypothesis was that biochar would promote wood decomposition (i.e., mass loss) more than manure because of its recalcitrance in the soil and its role in increasing soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…While climate variables are stronger predictors of wood stake decomposition in the northern hemisphere than soil properties (e.g., pH and C:N), microsite climatic conditions of soil temperature and moisture also influence wood stake decay (Risch et al., 2022). In general, warmer and moister conditions facilitate the wood decay process (Monroy et al., 2022; Piaszczyk et al., 2022). Our first hypothesis was that biochar would promote wood decomposition (i.e., mass loss) more than manure because of its recalcitrance in the soil and its role in increasing soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last three decades, it has been demonstrated that litter decay is influenced by a variety of chemical properties of the litter, including the litter N (Hobbie et al, 2012;Karki et al, 2022;Li et al, 2022), P and K concentrations and lignin content (Liu et al, 2022). However, Monroy et al (2022) suggested that in temperate regions, chemical properties may not be a good predictor of litter decomposability. Climatic factors like temperature, humidity and rainfall regulate the decomposition processes (Sanderman and Amundson, 2005;Kumar et al, 2021) and among these drivers rainfall pattern assert decomposition more than any other environmental drivers (Bradford et al, 2016;Steidinger et al, 2019).…”
mentioning
confidence: 99%